Serovars, virulence factors, and antimicrobial resistance profile of non-typhoidal Salmonella in the human-dairy interface in Northwest Ethiopia: A one health approach. - Achenef Melaku Beyene; Yismaw Alemie; Mucheye Gizachew; Ahmed E Yousef; Bereket Dessalegn; Abebe Belete Bitew; Amare Alemu; Waktole Gobena; Kornschober Christian; Baye Gelaw (Public Library of Science (PLoS), 2024)
Non-typhoidal Salmonella (NTS) is a zoonotic pathogen that exerts huge public health and economic impacts in the world. The severity of illness is mainly related to the serovars involved, the presence of virulence genes, and antimicrobial resistance (AMR) patterns. However, data are scarce on serovars, virulence genes, and AMR among NTS identified from the human-dairy interface in Northwest Ethiopia. Thus, this study investigated the serovars, common virulence genes, and AMR patterns of NTS isolates in the area. The study was conducted from June 2022 to August 2023 among randomly selected 58 dairy farms. A total of 362 samples were processed to detect NTS using standard bacteriological methods. The presumptive positive colonies were confirmed by Matrix-Assisted Laser Desorption Ionization-Time-of-Flight (MALDi-ToF). Polymerase chain reaction (PCR) was used to detect virulence genes, including invA and spvC. A slide agglutination test according to the White-Kauffmann-Le Minor scheme was employed to identify the serovars of the NTS isolates. The Kirby-Bauer disk diffusion method was used to assess the antimicrobial susceptibility patterns. Of the processed samples (362), 28 (7.7%) NTS isolates were detected. When distributed among samples, the proportions were 11.9%, 10.5%, 10.3%, 5.2%, 4.3%, and 1.7% among cows' feces, dairy farm sewage, pooled raw milk, milk container swabs, milkers' stool, and milkers' hand swab samples, respectively. Six serovars were detected with the dominancy of S. Uganda (39.3%), followed by S. enterica subsp. diarizonae (25.0%) and S. Typhimurium (21.4%). Among the 28 NTS isolates, 100% and 21.4% had the virulence genes invA and spvC, respectively. The susceptibility profile showed that 89.3% of the NTS isolates were resistant to at least one antimicrobial agent and 46.4% were resistant to three or more classes of antimicrobials (multidrug-resistant). Among antimicrobials, isolates were highly resistant to ampicillin (57.1%), followed by tetracycline (42.9%) and chloramphenicol (35.7%). On the other hand, the NTS isolates were 100%, 96.4%, and 96.4% susceptible to ceftriaxone, azithromycin, and norfloxacin, respectively. In conclusion, we detected NTS from humans, dairy cows, raw milk, dairy utensils, and the environment (sewage), showing the potential of the human-dairy farm-environment nexus in the NTS circulation. These further highlight that the interface is a good point of intervention in the control and prevention of NTS infection. The susceptibility profiles of the isolate necessitate interventions including the prudent use of the antimicrobials.